THE SYNTHESIS OF ION-IMPRINTED POLYMERS FOR SEPARATION AND ANALYSIS OF CHROMIUM(III) - Kurniawati, Fitri
Chromium is widely used in metallurgy for the production of steel, ferrous and non- ferrous alloys, in industrial processes for electroplating, tanning, metal smelting, and in the chemical industry for the production of paints and pigments. As a result, large amounts of chromium compounds are released into the environment causing contamination of soil, surface water and groundwater. Chromium exists in the environment generally in two oxidation states, as compounds Cr(III) and Cr(VI), which have different physicochemical, toxicological and biological properties. Cr(III) is an important micronutrient that has an important role in glucose, lipid and protein metabolism, while Cr(VI) has a detrimental effect on living organisms. Exposure to Cr(VI) compounds to living organisms can cause damage to the skin, respiratory tract, kidneys and increase the risk of lung cancer. The purpose of this research is to make Ion Imprinted Polymers Cr(III)-IIP so that it can be used for selective separation of Cr(III) and Cr(VI) metal ions. The research stage begins with the formation of a metal-ligand complex between the metal ion Cr(III) and the diphenylcarbazone ligand. Furthermore, prepolymerization occurs between the metal-ligand complex and the functional monomer methacrylic acid. In the presence of ethylene glycol dimethacrylate as a crosslinker and benzoyl peroxide as an initiator, thermal polymerization occurs. The mole ratio of template ion, monomer and crosslinker used in this study was 0.4:4:20. Control polymers, namely NIP (Non-Imprinted Polymers) and NIP-DPCO (Non-Imprinted Polymers- Diphenylcarbazone) were synthesized by the same procedure but without the presence of template ions. The synthesized polymers of Cr(III)-IIP, NIP and NIP- DPCO were then characterized using FTIR (Fourier Transform Infra Red) and SEM (Scanning Electron Microscope). From the FTIR spectra of the three sorbents, there is a strong and wide peak at a wave number of 3489 cm-1 and a moderate peak at a wave number of 1633 cm-1 which indicates the presence of a COOH group on the polymer surface. Strong peaks at wave numbers 1732 cm-1 and 1163 cm-1 indicate stretching vibrations -C=O and -C-O vibrations of methacrylic acid. The FTIR spectra of NIP and NIP-DPCO were similar to the spectra of Cr(III)-IIP which indicated the similarity in the main chain structure of the polymer. The results of SEM characterization showed that bulk polymerization caused the morphology of Cr(III)-IIP to be irregular in shape and large in size. However, the